2000
DOI: 10.1103/physrevlett.85.708
|View full text |Cite
|
Sign up to set email alerts
|

First Determination of Generalized Polarizabilities of the Proton by a Virtual Compton Scattering Experiment

Abstract: Absolute differential cross sections for the reaction ep-->epgamma have been measured at a four-momentum transfer with virtuality Q2 = 0.33 GeV2 and polarization epsilon = 0.62 in the range 33.6 to 111.5 MeV/c for the momentum of the outgoing photon in the photon-proton center of mass frame. The experiment has been performed with the high-resolution spectrometers at the Mainz Microtron MAMI. From the photon angular distributions, two structure functions which are a linear combination of the generalized polariz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 18 publications
8
65
0
Order By: Relevance
“…Our points connect smoothly to existing data, except to the (two independent) former measurements at Q 2 = 0.33 GeV 2 [4,6] which lie above the general trend. Somewhat in the spirit of our bin masking, which constrains the cross section to follow a well-defined q ′ cm -behavior, several fits were performed by the authors of the first VCS experiment [4] on their data at Q 2 = 0.33 GeV 2 , assuming different q ′ cm -evolutions of the cross section [23]. All the fits of [23], including the DR one, lead to an enhanced value for P LL − P T T /ǫ [and hence α E1 (Q 2 )], thus leaving the discrepancy unexplained for the electric GP.…”
Section: Lex and Dr Fitssupporting
confidence: 88%
See 2 more Smart Citations
“…Our points connect smoothly to existing data, except to the (two independent) former measurements at Q 2 = 0.33 GeV 2 [4,6] which lie above the general trend. Somewhat in the spirit of our bin masking, which constrains the cross section to follow a well-defined q ′ cm -behavior, several fits were performed by the authors of the first VCS experiment [4] on their data at Q 2 = 0.33 GeV 2 , assuming different q ′ cm -evolutions of the cross section [23]. All the fits of [23], including the DR one, lead to an enhanced value for P LL − P T T /ǫ [and hence α E1 (Q 2 )], thus leaving the discrepancy unexplained for the electric GP.…”
Section: Lex and Dr Fitssupporting
confidence: 88%
“…1 accomodates well the experimental data for α E1 (Q 2 ), which behave almost like a pure dipole. The baryon chiral pertur- , MAMI [4,6] and JLab [12]. Open and filled circles correspond to DR analyses; open and filled squares correspond to LEX analyses.…”
Section: Lex and Dr Fitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusive reaction is then identified using the missing mass squared of the undetected photon. Complementary information can be found in previous reviews [4][5][6][7][8][9]; details on apparatus and physics analyses can be found in the Thesis works [55][56][57][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and the experimental publications [7,11,[74][75][76][77][78][79][80][81][82][83].…”
Section: Methodsmentioning
confidence: 99%
“…The effect of such systematic errors is thus greatly reduced by adopting this renormalization procedure. Every VCS experiment having low-q ′ cm data utilized them to test the absolute normalization of the cross section, and to renormalize it if needed [7,[74][75][76][77][78]83]. By this method, the overall normalization uncertainty was reduced to, e.g., ± 1% in the MAMI-I experiment [57,74] and in the MAMI-VI experiment [83].…”
Section: Systematic Errorsmentioning
confidence: 99%